Interpersonal Communication Strategies of PAI Teachers in Enhancing Students' Learning Motivation at State High School 12 Medan - Anasa, Diva Puteri; Tambunanan, Nurhalima (Universitas Syiah Kuala, 2025)
This study aims to determine the implementation of PAI teachers' interpersonal communication strategies in increasing student learning motivation. The research method used is qualitative with observation, interview and documentation methods. The findings of the research results taken from interviews with teachers, students and principals were obtained strategies such as: 1) Teachers have created a positive learning environment, provided constructive rewards and feedback, set clear and measurable goals, used interesting learning methods, involved students in the learning process: adjusted learning to students' interests and needs increased student confidence, be a good example. 2) The strategies applied by teachers are not fully accepted well by students. 3) The impact obtained is that the strategy implemented is not in accordance with the criteria of students in this school